2014
DOI: 10.1021/nl5010493
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging of p–n Junction in Core–Shell GaN Wires

Abstract: While core−shell wire-based devices offer a promising path toward improved optoelectronic applications, their development is hampered by the present uncertainty about essential semiconductor properties along the threedimensional (3D) buried p−n junction. Thanks to a crosssectional approach, scanning electron beam probing techniques were employed here to obtain a nanoscale spatially resolved analysis of GaN core−shell wire p−n junctions grown by catalyst-free metal−organic vapor phase epitaxy on GaN and Si subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
102
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 57 publications
3
102
0
Order By: Relevance
“…On the contrary, EBIC offers excellent spatial resolution and allows to address individual nanostructures composing the macroscopic device. [8][9][10][11][12][13][14] In particular, EBIC microscopy is a perfectly dedicated tool to investigate the structural and the electrical properties of the three-dimensional nanostructured LEDs. In the past years, several EBIC investigations of single nanowires and nanowire devices built of different materials have been reported, [15][16][17][18][19][20] sometimes coupled with cathodoluminescence (CL) mapping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, EBIC offers excellent spatial resolution and allows to address individual nanostructures composing the macroscopic device. [8][9][10][11][12][13][14] In particular, EBIC microscopy is a perfectly dedicated tool to investigate the structural and the electrical properties of the three-dimensional nanostructured LEDs. In the past years, several EBIC investigations of single nanowires and nanowire devices built of different materials have been reported, [15][16][17][18][19][20] sometimes coupled with cathodoluminescence (CL) mapping.…”
Section: Introductionmentioning
confidence: 99%
“…19 Recently, Tchoulfian et al have proposed a cross-PAPER Nanoscale 2 | Nanoscale, 2015, 00, 1-- 3 This journal is © The Royal Society of Chemistry 2015 sectional approach based on cleaving core/shell nanowires along their axis, which has been applied to GaN p-n junction core-shell nanowires. 13 However no cross-sectional studies of full nanowire LEDs has ever been reported. In addition, no correlation between induced current and optical mapping has ever been performed on core/shell nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scanning transmission electron microscopy (STEM) using differential phase-contrast has also been proven to reveal the built-in electric field at a p-n junction7. Recent SEM characterizations of GaN nanorods have extended conventional mapping by adding in-situ electrical biasing thus enabling the direct imaging of the p-n junction under operational conditions and yielding critical information on its depletion width89. Other techniques like cathode-luminescence in a scanning transmission microscope (CL-STEM)10 and conductive atomic force microscopy (AFM) have also been utilized for the characterization of the p-n junction in GaN nanorods11 and porous GaN based LEDs12.…”
mentioning
confidence: 99%
“…We first note that the nitride bonding states can be viewed as Si atoms in Ga substitutional sites (Si Ga ), bonded to nitrogen, as expected in intentional n-doping with fully ionized, electrically-active dopants. The elemental silicon is representative of Si(-Si) 3 bonding or bonding of Si atoms with elements having similar electronegativity: the first situation would correspond to clustering of Si atoms already reported in GaN at very high doping levels [25]. In the second case Si atoms in nitrogen sites would be bonded directly to Ga of close (1.5) electronegativity to that of Si: this is again consistent with the N-deficient character of the m-facet surface as revealed by SAM and would tend to electrically compensate the expected n-type doping induced by Si Ga .…”
Section: Surface Chemistry Of the Doped Gan Wirementioning
confidence: 99%
“…Beyond the issues involved at the processing level, the physical characterization is often challenging because its deals with individual objects. It is also of utmost importance, within the perspective of a comprehensive understanding of the specific doping phenomena in wires, to develop reliable methods enabling to study individual wire structures [3]. Electrical (four-probe) and measurements on single wires are time consuming and with a limited spatial resolution.…”
Section: Introductionmentioning
confidence: 99%